2019
DOI: 10.1007/s11695-019-04166-y
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Cholecystectomy After Laparoscopic Roux-En-Y Gastric Bypass

Abstract: Background Patients who have undergone bariatric surgery are at risk for subsequent cholecystectomy. We aimed to identify risk factors for cholecystectomy after laparoscopic Roux-en-Y gastric bypass (LRYGB). Methods We conducted a retrospective case-control study of patients who underwent LRYGB between 2013 and 2015. Cases underwent cholecystectomy because of biliary symptoms after LRYGB. For each case, two controls were selected without subsequent cholecystectomy. Logistic regression analyses were used to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 26 publications
5
14
2
1
Order By: Relevance
“…The presence of a pain syndrome was also identified as risk factor for the occurrence of symptomatic gallstone disease after bariatric surgery, which is in line with our previous finding that a pain syndrome increases the chance of undergoing cholecystectomy after bariatric surgery [30] In our previous paper, we speculated that patients with a pain syndrome are more likely to visit a doctor in case they experience abdominal pain, often resulting in imaging of the abdomen. We all know that postoperatively, the probability to find gallstones during imaging is high.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The presence of a pain syndrome was also identified as risk factor for the occurrence of symptomatic gallstone disease after bariatric surgery, which is in line with our previous finding that a pain syndrome increases the chance of undergoing cholecystectomy after bariatric surgery [30] In our previous paper, we speculated that patients with a pain syndrome are more likely to visit a doctor in case they experience abdominal pain, often resulting in imaging of the abdomen. We all know that postoperatively, the probability to find gallstones during imaging is high.…”
Section: Discussionsupporting
confidence: 84%
“…Preoperatively, data on demographics, presence of comorbidity, and preoperative medication use were collected. Hypertension, type 2 diabetes, and pain syndrome were defined as earlier described [30]. Dyslipidemia was defined as the presence of at least one of the following: known dyslipidemia, use of lipid-lowering drugs, a high-density lipoprotein cholesterol ≤ 0.9 mmol/L, lowdensity lipoprotein cholesterol ≥ 5.0 mmol/L, total cholesterol ≥ 6.5 mmol/L, or triglycerides ≥ 5.0 mmol/L.…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, other reports found that gender was not associated with cholelithiasis after bariatric surgeries (6,10,16). However, others have shown that gender is a statistically significant risk factor for cholelithiasis development (8,17). Besides gender, age is a known risk factor; one study observed a higher mean age in patients who developed cholelithiasis (18); however, data on age and cholelithiasis development remain scarce.…”
Section: Discussionmentioning
confidence: 95%